Technology Leadership for Pandemic STEMgagement in Computer Science: A PK12 Case Study - Devery J. Rodgers (Education Sciences)
In this post-pandemic hybrid world of PK12 education, the onus is still on education leaders to close achievement gaps through equitable means. There are current socioeconomic, racial, gender, and geographical disparities that limit students’ full access to computer science education (CS). This case study reports how one urban PK12 school district in the United States is addressing the “leaky pipeline” with sustainable solutions for CS education with minoritized students. Using an online engagement framework, an ethnographic lens was used with document review, to conduct a content analysis of projects, programs, and services set up through the central office for nearly 20,000 students at the primary, middle grades, and secondary levels in computer sciences. Findings acknowledge leadership’s planning for student engagement in STEM+C (science, technology, engineering, math and computer science) for virtual instruction. This study will contribute to the burgeoning knowledge of leadership for CS activities in PK12, and serve as a beacon for learning organizations bolstering CS activities in the future.